Autoimmune hemolytic anemia: Case review - María Nazaret Sánchez; Josune Zubicaray; Elena Sebastián; Eva Gálvez; Julián Sevilla (Elsevier, 2021)
Introduction: Autoimmune hemolytic anemia (AIHA) is a rare and generally self-limiting disease in children. Material and methods: A descriptive cross-sectional study was performed in children under 18 years diagnosed with AIHA from January 1997 to July 2019. Clinical variables were collected and AIHA was classified according to the direct antiglobulin test (DAT) in warm AIHA (IgG+/-C3d) and cold AIHA (C3d). Response to treatment and evolution were analyzed. Results: 25 patients were included and 72% were males. The median age at diagnosis was 2 years (range 0.4-9). Fever (72%), pallor (68%), jaundice (64%), hepatosplenomegaly and coluria (48%) were the most common presenting symptoms. The median hemoglobin at diagnosis was 5.4 g/dl. DAT was positive in 96%, with detection of IgG antibodies in 76%. A single case presented negative DAT. 20% of the patients associated another cytopenia, one of which was subsequently diagnosed with common variable immunodeficiency. Concomitant viral infection was suspected or documented in 32%. Most of the cases were self-limiting and responded to corticosteroid treatment (72%). Those with partial response (24%), mainly those associated with other cytopenias, required other lines of treatment (rituximab, mycophenolate, immunoglobulins,...). Complications (32%) and relapses (26%) were detected only in warm AIHA. Conclusions: Our case series confirms that AIHA is a very rare disease in childhood. Most cases evolve favorably, although up to a quarter of them require second lines of treatment and, in exceptional cases, they need very aggressive treatments. These latter cases generally correspond to patients who present more than one cytopenia in the course of the disease. Resumen: Introducción: La anemia hemolítica autoinmune (AHAI) es una enfermedad rara en niños, generalmente autolimitada. Material y métodos: Estudio descriptivo transversal en menores de 18 años diagnosticados de AHAI desde enero 1997 a julio 2019. Se recogieron variables clínicas y se clasificaron según el test de Coombs directo (TCD) en AHAI por anticuerpos calientes (IgG+/-C3d) y fríos (C3d). Se analizó la respuesta al tratamiento y su evolución. Resultados: Se incluyeron 25 pacientes, siendo el 72% varones. La mediada de edad al diagnóstico fue 2 años (rango 0,4-9). Los síntomas predominantes fueron fiebre (72%), palidez (68%), ictericia (64%), hepatoesplenomegalia y coluria (48%). La mediana de hemoglobina al diagnóstico fue 5,4 gr/dl. En el 96% el TCD fue positivo, con detección de anticuerpos IgG en el 76%. Un solo caso presentó TCD negativo. Un 20% asociaron otra citopenia, uno de ellos fue diagnosticado posteriormente de inmunodeficiencia variable común. En un 32% se sospechó o documentó una infección viral concomitante. La mayoría de los casos fueron autolimitados y respondieron a tratamiento con corticoides (72%). Aquellos con respuesta parcial (24%), principalmente los que asociaban otras citopenias, precisaron otras líneas de tratamiento (rituximab, micofenolato, inmunoglobulinas,...). Se detectaron complicaciones (32%) y recaídas (26%) únicamente en AHAI por anticuerpos calientes. Conclusiones: Nuestra serie confirma que la AHAI es una enfermedad muy poco frecuente en la infancia. La mayoría de los casos evolucionan favorablemente, aunque hasta una cuarta parte precisan segundas líneas de tratamiento y casos excepcionales tratamientos muy agresivos. Estos últimos suelen corresponder a pacientes con más de una citopenia en la evolución de la enfermedad.